On the human right to food security - Gabdulbarovna Demieva, Ainur; Vladimirovich Iroshnikov, Denis; Alekseev, Kirill Vasilievich (Opción, 2019)
The article analyzes the right to food security in the human rights system. In particular, the author analyzes the place of this right in the existing generations of human rights, as well as in connection with the right to development via the dialectical method of scientific knowledge. As a result, the Food Security Act of India enshrines the right to food for all inhabitants of the country as a legitimate right. In conclusion, today the issue of enforcement of the human right to food security is very complex, requiring detailed scientific study and serious research.